2014
DOI: 10.5539/ijef.v6n5p182
|View full text |Cite
|
Sign up to set email alerts
|

Diversification as a Corporate Strategy and Its Effect on Firm Performance: A Study of Zimbabwean Listed Conglomerates in the Food and Beverages Sector

Abstract: Portfolio diversification in capital markets is an accepted investment strategy. On the other hand corporate diversification has drawn many opponents especially the agency theorists who argue that executives must not diversify on behalf of share holders. Diversification is a strategic option used by many managers to improve their firm's performance. While extensive literature investigates the diversification performance linkage, little agreements exist concerning the nature of this relationship. Both theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(56 reference statements)
3
3
0
2
Order By: Relevance
“…Lastly, the results also showed that there's a significant positive relationship between diversification strategies and organizational performance (β=0.408, p=0.001<0.05) meaning that if commercial printing firm increases the use of diversification strategy by one unit, consequently their profit growth would improve significantly at a unit of 0.408.The findings corresponds with that of Eukeria and Favourite (2014) on the study of…”
Section: Regression Analysis Between Growth Strategies and Profit Growthsupporting
confidence: 80%
See 1 more Smart Citation
“…Lastly, the results also showed that there's a significant positive relationship between diversification strategies and organizational performance (β=0.408, p=0.001<0.05) meaning that if commercial printing firm increases the use of diversification strategy by one unit, consequently their profit growth would improve significantly at a unit of 0.408.The findings corresponds with that of Eukeria and Favourite (2014) on the study of…”
Section: Regression Analysis Between Growth Strategies and Profit Growthsupporting
confidence: 80%
“…It however contradicts with that of on the study of effect of product development strategy on performance in sugar industry in Kenya which revealed a weak relationship between product development strategy and all aspects of performance. Lastly, the regression results also showed that there's a significant positive relationship between sales growth of commercial printing firms and diversification (β=0.356, p=0.001<0.05) implying that a unit increase in diversification strategies would significantly improve the sales growth of commercial printing firms at a unit of 0.356.The findings corresponds with that of Eukeria and Favourite (2014) on the study of Diversification as a Corporate Strategy and Its Effect on Firm Performance who found out that diversification and performance ( as measured by turnover percentage growth) were linearly and positively related. The ANOVA sought to show significance of the regression model.…”
Section: Inferential Statisticssupporting
confidence: 72%
“…Level diversifikasi perusahaan memperlihatkan besar konsentrasi suatu entitas usaha dalam segmen usaha yang dimilikinya (Setionoputri et al, 2007). Penelitian yang dilakukan oleh Li & Wong (2003), Sari (2009), Eukeria & Favourate (2014), Wisnuwardhana & Diyanty (2015), dan Fadillah (2018) hasilnya menerangkan bahwa diversifikasi memiliki pengaruh positif terhadap kinerja perusahaan. Sedangkan hasil penelitian Rumelt (1977), Lang & Stulz (1994), Jiraporn et al, (2006), Shinta Heru Satoto (2009, Lucyanda et al, (2010), Amyulianthy & Sari (2013), Sari et al, (2014) kepentingan untuk mendapatkan insentif atau reward dari perusahaan, sehingga ini menjadi dorongan bagi manajemen untuk memperluas usaha dengan cara diversifikasi.…”
Section: Sumber: Data Olahan Penelitiunclassified
“…Selain untuk meningkatkan nilai pemegang saham, perusahaan yang memilih untuk melakukan strategi diversifikasi terkait memiliki tujuan untuk dapat memiliki cost advantage dibandingkan pesaingnya, seperti yang dilakukan oleh PT. Indofood Sukses Makmur Tbk yang menyediakan produk tepung ketika mereka juga menjual produk mie instan, sehingga tentunya produk mie instan PT Indofood Sukses Makmur Tbk memiliki cost advantage dibandingkan dengan produk pesaing perusahaan lainnya (Eukeria dan Favourate, 2014).…”
Section: Pendahuluanunclassified